Logaritmic Fuzzy Preference Programming Approach for Evaluating University Ranking Optimization - Wahyuningrum, Tenia; Pandiya, Ridwan (Scientific Journal of Informatics, 2017)
Assesing quality university’s website trough webometrics is becoming one of many measures in World Class University. To get good grades, so that it can compete with other universities in the world, it needs to be pursued strategies based on the achievement of the perspective of cost (expenses) and the condition of the availability and readiness of human resource (HR owned) by the institution. Webometrics ranking optimization tailored to the institutional capacity is absolutely necessary, in order to achieve the expected goals effectively and fuel-efficient. Therefore, this paper discussed the application of the Analytical Hierarchy Process with Logarithmic Fuzzy Preference Programming combination proved to covered of the methods FPP on the university web ranking optimization. From the results of sub-criteria weighting based on the perspective of cost and human resources, earned the highest ranking among other factors recommended monitoring the ranking of sites ahrefs (C332) and majesticseo (C331) as well as increasing the number of links from other websites (C321).